The Chinese Export Boom: An Examination of the Detailed Trade Data. (17th January 2013) - Berger, Brett; Martin, Robert F.
Abstract From 2000 to 2007, Chinese exports grew at a phenomenal pace. Our paper uses finely detailed Chinese export data (8‐digit Harmonized Commodity Description and Coding System codes) combined with US trade data to explore how this was achieved. Although general explanations such as China's exchange rate policy no doubt played a role, we find that sector‐specific stories, effective Chinese industrial policy and fortuitous timing were more critical. The detailed trade data reveal that "new" technology goods, such as cell phones, LCD screens and laptops, played a key role. Finally, we use the data to examine the relationship between Chinese exports and global manufacturing, in particular US manufacturing employment. We find that competition from China in both domestic and foreign markets likely contributed to a significant decline in USA manufacturing employment, but that relatively low US investment and slow GDP growth in the US following the 2001 recession played an equally important role.